Multifactorial Induction of a “Scleroderma‐Like Pattern” Without Underlying Connective Tissue Disease: Diagnostic and Therapeutic Implications - Angelo Nigro (ACR Open Rheumatology)
A 60‐year‐old man with a significant 20‐year history of smoking, averaging approximately 20 cigarettes per day, presented with type 2 diabetes mellitus, hypercholesterolemia, and hypertension. Over the preceding three months, the patient reported recurrent episodes of acrocyanosis and erythema of the hands that were primarily induced by cold exposure. A capillaroscopy conducted in November 2024 revealed a “scleroderma‐like pattern” that was characterized by enlarged capillaries, megacapillaries, and a capillary density of fewer than eight capillaries per millimeter. Comprehensive immunologic and instrumental assessments demonstrated no evidence of systemic involvement or autoimmune disease. This case emphasizes the need to recognize the substantial role of cardiometabolic risk factors, including smoking, diabetes, hypertension, and hypercholesterolemia, in contributing to capillaroscopic abnormalities that may mimic systemic sclerosis. In this patient, the cumulative impact of these cardiometabolic factors culminated in the establishment of an “scleroderma‐like pattern” observed on nailfold capillaroscopy.